(untitled) (Research, Society and Development, 2021)
Objectives: to understand the confluences of Viktor Frankl’s theory of "search for meaning" with the formation of values ​​arising from the process of Permanent Education in Health and, thus, propose a reflection on their contributions on the search and discovery/encounter with the meaning of life of the frontline health care workers of COVID-19. Methodology: theoretical-reflective study based on vulnerability and confrontations with the awakening of the meaning of life of frontline health care workers of COVID-19, based on the analysis of Viktor Frankl’s “search for meaning” theory. Results: the uncertainty, grief and challenges posed by the pandemic can lead those who face it daily to continuous suffering, hopelessness and loss of the meaning of life. In the search for meaning, a radical change in attitudes towards life is necessary, especially in a situation of suffering. In this context, Permanent Education in Health presents itself as a tool capable of transforming specific activities into the energy of educational activities and, along with the frontline health care workers of COVID-19, it offers essential elements to build and to interfere in the practical reality and in the identifying with the will to meaning. Final considerations: Viktor Frankl’s theory of the “search for meaning” highlights the importance of implementing Permanent Education in Health for COVID-19 frontline workers, with regard to the construction and attribution of the meaning of life.